The analytical method for determining the parameters of impulse overvoltages from atmospheric discharges - Marković Nenad; Bjelić Slobodan; Marković Strahinja (Bakar, 2025)
Impulse generators with RC circuits form the foundation for producing surge voltages used in high-voltage equipment testing. In high-voltage engineering literature, the expressions for impulse voltage waveforms include known parameters of lightning or switching overvoltages, which are used to determine the amplitudes and time constants of impulse overvoltages in RC discharge circuits. However, both standards and scholarly publications often lack clarification for various ambiguities-such as the commonly cited factor of 1.67 for rise time-without providing rigorous physical or mathematical justification. All overvoltage parameters are typically defined axiomatically, and the existing formulas for designing impulse voltage generators are often inadequate. This paper presents implemented formulas and derived solutions that enable accurate determination of all parameters and electrical quantities of an RC circuit generating a specified impulse voltage waveform. For method verification, an adapted module of the MATLAB simulation package, psbsurgeovervoltage.mdl, was employed.